Consecutive Hypoxia Decreases Expression of NOTCH3, HEY1, CC10, and FOXJ1 via NKX2-1 Downregulation and Intermittent Hypoxia-Reoxygenation Increases Expression of BMP4, NOTCH1, MKI67, OCT4, and MUC5AC via HIF1A Upregulation in Human Bronchial Epithelial Cells - Yang, Yung-Yu; Lin, Chao-Ju; Wang, Cheng-Chin; Chen, Chieh-Min; Kao, Wen-Jen; Chen, Yi-Hui (Frontiers in Cell and Developmental Biology, 2020)
Previous studies have shown that the experimental models of hypoxia-reoxygenation (H/R) mimics the physiological conditions of ischemia-reperfusion and induce oxidative stress and injury in various types of organs, tissues, and cells, both in vivo and in vitro, including human lung adenocarcinoma epithelial cells. Nonetheless, it had not been reported whether H/R affected proliferation, apoptosis, and expression of stem/progenitor cell markers in the bronchial epithelial cells. In this study, we investigated differential effects of consecutive hypoxia and intermittent 24/24-hour cycles of H/R on human bronchial epithelial (HBE) cells derived from the same-race and age-matched healthy subjects (i.e., NHBE) and subjects with chronic obstructive pulmonary disease (COPD) (i.e., DHBE). To analyze gene/protein expression during differentiation, both the NHBE and DHBE cells at the 2nd passage were cultured at the air-liquid interface (ALI) in the differentiation medium under normoxia for 3 days, followed by either culturing under hypoxia (1% O2) for consecutively 9 days and then returning to normoxia for another 9 days, or culturing under 24/24-hour cycles of H/R (i.e., 24 hours of 1% O2 followed by 24 hours of 21% O2, repetitively) for totally 18 days, so that all differentiating HBE cells were exposed to hypoxia for a total of 9 days. In both the normal and diseased HBE cells, intermittent H/R significantly increased HIF1A, BMP4, NOTCH1, MKI67, OCT4 and MUC5AC expression, while consecutive hypoxia significantly decreased NKX2-1, NOTCH3, HEY1, CC10 and FOXJ1 expression. Inhibition of HIF1A or NKX2-1 expression by siRNA transfection respectively decreased BMP4/NOTCH1/MKI67/OCT4/MUC5AC and NOTCH3/HEY1/CC10/FOXJ1 expression in the HBE cells cultured under intermittent H/R to the same levels under normoxia. Overexpression of NKX2-1 via cDNA transfection caused more than 2.8-fold increases in NOTCH3, HEY1 and FOXJ1 mRNA levels in the HBE cells cultured under consecutive hypoxia compared to the levels under normoxia. Taken together, our results show for the first time that consecutive hypoxia decreased expression of the co-regulated gene module NOTCH3/HEY1/CC10 and the ciliogenesis-inducing transcription factor gene FOXJ1 via NKX2-1 mRNA downregulation, while intermittent H/R increased expression of the co-regulated gene module BMP4/NOTCH1/MKI67/OCT4 and the predominant airway mucin gene MUC5AC via HIF1A mRNA upregulation.